Numerical modelling of the impact of coral reef degradation and sea level rise on coastal protection at The Buccoo Reef, Tobago: implications for reef restoration and management strategies - Boodoo, Avinash; Villarroel-Lamb, Deborah (Frontiers in Marine Science, 2025)
Coral reefs provide natural coastal protection through depth-induced wave breaking and frictional dissipation on the fore reef, the reef crest, and the back reef. The coral reef roughness is a significant factor in wave attenuation through frictional dissipation and is directly linked to the reef’s health. The influence of reef roughness on frictional dissipation under representative conditions, and the extent to which coral reef degradation and Sea Level Rise (SLR) reduces this coastal protection service remains underexplored, especially at coastal sites in Caribbean Small Island Developing States. A numerical modelling approach using a coupled depth-averaged (2DH) hydrodynamic and spectral wave model in Delft3D was used to evaluate the coastal protection effectiveness of a fringing reef under varying scenarios of coral reef degradation and SLR at The Buccoo Reef, Tobago. Using near present day conditions as the baseline scenario, assessed wave conditions showed 100% and 96.45% reductions at low and high tides respectively. Under modelled degraded reef conditions on the reef flat, wave heights increased by an average of 21.74% compared to baseline conditions, while for modelled healthier reefs, there was an 18.9% decrease in wave heights from the baseline scenario. Using various SLR scenarios, wave heights showed increases over baseline conditions between 160.5% and 388.4% for increases in sea level from 0.25 m to 1.00 m. The results highlight the importance of the frictional dissipation provided by healthy coral reefs, with degraded corals and rising sea levels leading to substantial increases in nearshore wave heights which could exacerbate issues such as coastal erosion and flooding. Management strategies such as Integrated Coastal Zone Management (ICZM) and innovative approaches such as the deployment of artificial reefs which are specifically designed to replicate the complex structure and roughness of natural reefs can contribute to wave attenuation by frictional dissipation.